Preliminary study on mathematical problem solving ability of junior high school students on the triangle subject - D R Ningsih; E Nurlaelah; A Jupri (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
The triangle subject is a part of geometry concept. The subject is important to bemastered if a student wants to develop the geometrical ability. However, in the fact, someresearch reveal that Mathematical problem solving ability of students is still low becausestudents are not yet accustomed to solve mathematical problems yet. The purpose of this studyto determine the ability of mathematical problem solving students in junior high school on thetriangle subject. This study was conducted by using descriptive qualitative method. The samplein this study is consisted of 32 students in the grade IX which was taken with purposivesampling technique. Data were collected through the test which consists of three essayquestions based on the indicators: (1) identify the adequacy of the data; (2) create amathematical model of daily problems and solve it; (3) select and implement strategies to solvemathematical problems; (4) interpret the results according to the origin of the problem and dothe verification. The results of this study indicate that students difficulties in problem solving,and every student has different levels of mathematical problem solving ability.